Studi Hasil Pemeriksaan Kolesterol Pada Perokok Usia Lanjut Di Rsud Syekh Yusuf Kabupaten Gowa - Kasmiati Kasmiati; Idris Mone; Nursan Nursan (Jurnal Media Laboran, 2017)
Cholesterol is one of the soft fat compounds, yellow and like wax produced by the body, especially in the liver. Cholesterol is closely related to smoking because smoking can reduce good cholesterol, so that circulating in the body only bad cholesterol. This bad cholesterol if not controlled can be fatal, especially in elderly smokers whose endurance has decreased. The purpose of this study was to find out how the results of the examination of cholesterol levels in elderly smokers in Syekh Yusuf Hospital Gowa Regency. This type of research is a type of laboratory experimental research that is descriptive in nature, namely conducting laboratory tests to determine the results of cholesterol examination in elderly smokers using 10 samples. The results showed that cholesterol levels in elderly smokers were normal or no significant increase and decrease because the patient's immune system was in good condition.